Emotional Intelligence in Frontline Managers’ Leadership Practices - Virta, Emma (My University, 2023)
The purpose of this master’s thesis is to continue the Leadership research at the University of Vaasa on how Emotional Intelligence (EI) appears in Leadership, and to obtain a more comprehensive picture of Frontline Managers’ (FLM) use and perceptions of EI in Leadership. The data was collected by interviewing eight (8) FLMs working in small and medium-sized firms. The theoretical framework of the study consists of previous research on Leadership and EI, and the interview framework was designed using the theories of previous studies. One of the objectives of the study was to find out how EI is displayed among FLMs today. The second objective was to investigate how FLMs perceive the importance of EI in Leadership. The data was processed using content analysis and answers relevant to the research questions were classified by using thematization and typification. The findings show that the interviewees use all the different competencies of EI in their Leadership. However, self-management and empathy were particularly prominent. The answers showed that the FLMs use EI as a tool in situational leadership, and that competencies of EI evolve hierarchically or in relation to other EI competencies. FLMs consider EI a crucial part of leadership, but they face challenges regarding relationship management. The results of the study can primarily be utilised when considering how FLMs' EI can be developed in pursuit of effective leadership. The results of the study also support previous research on the occurrence of EI in FLMs' leadership. The results raise a question on whether FLMs get enough support and training for practising more challenging EI competencies that could be useful for example in conflict management. EI has various antecedents on Leadership, and Leadership strongly affects individuals, organizations, and society. Therefore, the results also raise a question on what kind of outcomes and possibilities supporting and training FLMs’ EI could create for different stakeholders.
Keywords: emotional intelligence; leadership (activity); social skills; situational awareness; self-awareness; empathy; managerial work; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business